Analisis Kesalahan Penggunaan Tanda Baca dalam Karangan Teks Eksplanasi Siswa Kelas V SD Negeri Tombolo. K Kecamatan Pallangga Kabupaten Gowa - Nurul Fadhillah; Andi Adam; Abdan Syakur (Jurnal Bintang Pendidikan Indonesia, 2025)
The main problem in this study is how the errors in the use of punctuation in the explanatory text composition of class V students of SD Negeri Tombolo. K and aims to find out the description of the errors in the use of punctuation in the explanatory text composition of class V students of SD Negeri Tombolo. K. This type of research is qualitative descriptive research. The data and data sources in this study are the explanatory text compositions of class V students of SD Negeri Tombolo. K, Gowa Regency. The instruments used in this study were observation, interviews, and data from the results of students' explanatory text compositions. The results of the study showed that the results of the compositions analyzed using descriptive analysis were still partly found errors in the use of punctuation. It can be seen from the percentage of errors in the use of period punctuation 59.09%, comma punctuation 21.21%, hyphen punctuation 12.12%, quotation marks 4.54%, and quotation marks 3.03%. Based on the results of the study, it can be concluded that errors in writing the use of punctuation in students' explanatory text compositions are still found errors in writing the use of punctuation, especially in period and comma punctuation.